Study of The Influence of Social Media on Adolescent Behavior in Medan City in 2025 - Mian Ivany Banjar Nahor; Alicya Elisabet Simamora; Elisa Gurning; Putri Sosanti Sembiring (Journal Social Humanity Perspective, 2026)
This study aims to analyze the influence of social media on adolescent behavior in Medan City in 2025. Using a quantitative method with a descriptive correlational approach, the research involved 100 adolescent respondents aged 13–20 years. The results show that the majority of adolescents use social media for more than 4 hours per day, with Instagram, TikTok, and YouTube as the main platforms. Social media provides positive impacts such as increased creativity, expanded social networks, and educational benefits. However, negative impacts were also found, including decreased study concentration, consumptive behavior, cyberbullying, and reduced direct social interaction. Parental supervision and digital literacy programs in schools have proven effective in mitigating these negative effects. This study recommends strengthening digital literacy, enhancing the role of parents, and developing responsible social media usage policies among adolescents.